Pengaman File Video Menggunakan Algoritma Merkle Hellman Knapsack - Soeb Aripin; Muhammad Syahrizal (STMIK Budi Darma, 2020)
The issue of security and confidentiality is one important aspect of a message, data or information. In this case it is closely related to how important the message, data, or information is sent and received by parties or people concerned, whether the message, data, or information is still authenticity. At present there are many conveniences in downloading and uploading videos that make videos vulnerable to hijacking, especially if the video is an important and highly confidential video, so an application that is able to encode this important video is needed so that its security can be protected from unauthorized people, except for people who are entitled to. The security technique used by the author in this study uses cryptographic technology. To be able to do well, we need an algorithm for encryption and decryption. The algorithm used here is the Merkle Hellman Algorithm. This Algortman can be used on a video file is something that needs to be considered in maintaining the confidentiality of the data itself, especially if the video file can only be known by certain parties. There are many ways of approach taken to realize the confidentiality of the data starting from security or protection. physical to the form of a mathematical-based algorithm that makes the data illegible. So that the data in it cannot be easily known by unauthorized parties and only the intended video file recipient is able to decipher the video file